2018
DOI: 10.1093/gerona/gly032
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function, Consent for Participation, and Compliance With Wearable Device Protocols in Older Adults

Abstract: Impaired cognition does not seem to be a barrier to compliance with simply wearing a device but may affect compliance with additional action such as pressing event markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…Study participants with cognitive function in the normal to mild dementia range have overall good compliance. 10 , 28 However, studies including participants with mild to moderate dementia found compliance decreased with participants’ cognitive ability, 29 , 30 which is contrary to our finding that participants with the worst cognitive function as indicated by FAST score had better compliance. The marginal sex difference found in our study may partly explain the contradictory results as the two female participants with the worst compliance had better functionality/cognition (FAST score 6a and 6d, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…Study participants with cognitive function in the normal to mild dementia range have overall good compliance. 10 , 28 However, studies including participants with mild to moderate dementia found compliance decreased with participants’ cognitive ability, 29 , 30 which is contrary to our finding that participants with the worst cognitive function as indicated by FAST score had better compliance. The marginal sex difference found in our study may partly explain the contradictory results as the two female participants with the worst compliance had better functionality/cognition (FAST score 6a and 6d, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…Providers' perceptions of the barriers that patients and research participants may face (e.g., age, potential adherence) or perceptions of the risks of research to their patients (e.g., risk of toxicity of an experimental treatment) may limit their referral of older adults to research studies [22,24,30,31]. Some older adults may also not be mentally competent or physically well enough to consent to or adhere to research protocols [28,29,[32][33][34][35]. Individuals eligible for studies have also cited family and friend opposition or perceived burden on caregivers as barriers to participation [22,28].…”
Section: Older Adultsmentioning
confidence: 99%
“…This analysis is limited to those born between 1920 and 1947 (n = 759) (Figure 1), the initial birth-year range. Agreement to participate in the Sleep Study and return of actigraphy data were not themselves related to cognitive function (22).…”
Section: Study Populationmentioning
confidence: 99%